PENGARUH MODEL PEMBELAJARAN OUTDOOR EDUCATION TERHADAP KETERAMPILAN MOTORIK - Ary Suud Cahyo Alben; Ali Mardius; Ilham Ilham (Jurnal Muara Olahraga, 2022)
Abtract This research is to discuss the influence of outdoor education learning models on motor development which is still very rare. The purpose of this study aims to provide information about the influence of outdoor education learning models on motor development. Methodology This study uses the literature review method using a comprehensive strategy such as searching for articles in the research journal database. The databases used are Scopus, Web of Science, and Google Scholar. The results of the literature review show that outdoor education has a positive impact on motor development. Outdoor education can be done by modifying it in the form of a game, making a special program, and making it a school curriculum to improve motor skills. Keywords: Learning, Outdoor Education, Motor.